Evaluating the Best Renewable Energy Technology For Sustainable Energy Planning - Demirtas, Ozgur (International Journal of Energy Economics and Policy, 2013)
Energy is one of the main factors that must be considered in the discussions of sustainable development. The basic dimensions of sustainability of energy production are environmentally, technically, economically and socially sustainable supply of energy resources that, in the long term, is reliable, adequate and affordable. Renewable, clean and cost effective energy sources are preferred but unfortunately no one of the alternative energy sources can meet these demands solely. So, the problem of determining the sustainable energy planning is a strategic tool for the development. In this dissertation, the aim of this study is to determine the best renewable energy technology for sustainable energy planning. For this aim, we used AHP methodology, which is a multi-criteria decision making (MDCM) method. In the proposed method, the weights of the selection criteria are determined by pairwise comparison matrices of the AHP. Results indicate that wind energy is the most appropriate renewable energy option in this study. Future researches could be conducted based on different multi-criteria decision-making techniques such as ANP, fuzzy ELECTRE or fuzzy TOPSIS for comparative purposes. Keywords: Renewable Energy; Sustainable Energy Planning; AHP; Multi-Criteria Decision Making JEL Classifications: Q0; Q2; Q4